MEDSEA-FIN: A DSGE model of the Maltese economy with housing and financial frictions - William Gatt; Noel Rapa; Luca Brugnolini (Central Bank of Malta, 2020)
We extend the Central Bank of Malta's core DSGE model - MEDSEA - with housing and financial frictions to capture the important theoretical links betweeen house prices, credit and consumption. The model features a rich set of features that are inherent to small open economies in a monetary union. We add a borrowing constraint on a subset of households that is contigent on the value of housing wealth and a maximum loan-to-value (LTV) ratio. We also impose capital requirements on the financial intermediary through a minimum capital-to-assets ratio (CAR) constraint. These two requirements form the basis of a typical macroprudential regime in a developed economy. We show how the macroprudential authority can dampen the rise in credit and consumption during a credit boom by using these two policy tools to 'lean against the wind'. MEDSEA-FIN is therefore tailored to study macro-financial issues related to housing and credit, and the adequate policy responses.
Keywords: C54; E44; E58; E60; 330; borrowing constraints; loan-to-value ratio; capital-to-assets ratio; macroprudential policy